Supporting mobile multimedia applications through adaptive middleware. - Coulson, G. (IEEE Journal on selected areas in communications)
The traditional approach to developing middleware platforms is to adopt a ?black box? philosophy whereby the platform offers a fixed programming model to applications together with fixed per-platform implementations. In this paper, we describe research which is exploring an open approach to the implementation of middleware platforms. Our motivation is to accommodate the demanding requirements for quality-of-service (QoS) adaptation as imposed by mobile multimedia applications. We use an extended CORBA computational model featuring the concept of explicit open bindings. This provides an architectural framework for openness and QoS adaptation. The paper concludes by considering the more general application of an open systems philosophy; in particular, we introduce the concept of reflective middleware